(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
The laxity and poor job performance of many academic staff in Colleges of Education (COEs) in Delta State which has become worrisome especially in this digitalized era, necessitated this present study. This study explored the awareness and utilization of ChatGPT Artificial Intelligence (AI) by academic staff for enhancing their job performance in COEs in Delta State. The purpose of this study was to determine the level of awareness, percentage level of utilization and current pattern of ChatGPT (AI) usage among academic staff in Delta State COEs. As such, three research questions guided this study. A descriptive survey research design was adopted in the study. Population for the study constituted 729academic staff from two colleges of education (COE)in Delta State. The sample size for the study comprised a total of 365 academic staff selected at 50% from their entire population using proportionate stratified random sampling technique. A research instrument constructed by the researchers and titled: “Exploring Awareness and Utilization of ChatGPT Artificial Intelligence (AI) for Enhancing Academic Staff Job Performance Questionnaire (EAUCGPTAIEASJPQ)” containing 33 items was used for data collection. The questionnaire was structured on different rating scales. Both validity and reliability of the questionnaire were established. Data collated were analyzed using mean statistics rated at 2.50 and standard deviation. Findings of the study indicated among others that; the academic staff were only aware of ChatGPT (AI) in certain areas, but were not aware of ChatGPT (AI) in majority of the areas investigated in order to enhance their job performance in the COEs in Delta State. They did not also utilize ChatGPT for enhancing their job performance in the COEs. The study recommended among others that the college management in collaboration with the National Commission for Colleges of Education (NCCE) and financial assistance from the Federal and State governments, should prioritize comprehensive training programmes and on-going professional development through workshops, seminars, online courses and hands-on sessions to familiarize academic staff with ChatGPT AI practical applications in educational context and create awareness to them concerning the importance of exploring this new technology for enhancing their job performance and building their capacity for effective utilization.